2021
DOI: 10.1007/s10643-021-01224-y
|View full text |Cite
|
Sign up to set email alerts
|

Early Childhood Educators’ Perceptions of Their Emotional State, Relationships with Parents, Challenges, and Opportunities During the Early Stage of the Pandemic

Abstract: This article presents a study about the impact of COVID-19 on childcare center educators in Quebec (Canada). Regulated childcare services were closed due to the pandemic between March 16 and May 31, 2020, in areas considered "hot" (highly affected by the pandemic). During this time, some centers were transformed into "emergency childcare services" available to parents considered to be essential workers. Therefore, few children attended, and most educators worked remotely. In May 2020, 372 educators completed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…On the other hand, teachers' level of job satisfaction [39,71], positive affect [62], dispositional joy and buoyance in teaching [62], ICT self-efficacy [74], self-efficacy [35,72], sense of control [75], attitudes about online education [74], the perceived supervisor support [74], self-rated health [68], work stability [46], motivation for professional development [73], and psychological needs for autonomy, competence and relatedness [75] were found to be negatively associated with teachers' perceived stress. In addition, risk factors associated with teachers' increased odds of developing anxiety symptoms included: conducting face-to-face teaching [57,76], having low motivation for online teaching [65]; having no experience in online teaching [66]; raising vocal loudness when conducting online-teaching [58]; experiencing family-work conflict [71], having caregiving responsibilities [46,54,66]; had developed COVID-19 related symptoms [70]; had a relative or friend died from COVID-19 [70]; and having chronic pathology or living with others with chronic pathology [47].…”
Section: Other Associated Factors Of Teachers'mentioning
confidence: 99%
“…On the other hand, teachers' level of job satisfaction [39,71], positive affect [62], dispositional joy and buoyance in teaching [62], ICT self-efficacy [74], self-efficacy [35,72], sense of control [75], attitudes about online education [74], the perceived supervisor support [74], self-rated health [68], work stability [46], motivation for professional development [73], and psychological needs for autonomy, competence and relatedness [75] were found to be negatively associated with teachers' perceived stress. In addition, risk factors associated with teachers' increased odds of developing anxiety symptoms included: conducting face-to-face teaching [57,76], having low motivation for online teaching [65]; having no experience in online teaching [66]; raising vocal loudness when conducting online-teaching [58]; experiencing family-work conflict [71], having caregiving responsibilities [46,54,66]; had developed COVID-19 related symptoms [70]; had a relative or friend died from COVID-19 [70]; and having chronic pathology or living with others with chronic pathology [47].…”
Section: Other Associated Factors Of Teachers'mentioning
confidence: 99%
“…These pandemic-induced changes meant fewer opportunities for teachers to talk with parents. Research shows that communication between childcare teachers and caregivers is critical to both parties (Bigras et al, 2021 ). Parents who were home-bound during the pandemic found that teacher communication–in terms of suggestions for age-appropriate activities–helped parents cope with stress (Zhang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that children and families benefited from the pandemic-induced changes in center-parent communication (Soltero-Gonzalez & Gillanders, 2021 ; Bigras et al, 2021 ; Linnavalli & Kalland, 2021 ). Enrolling children in childcare during the pandemic appeared to benefit parent-child relationships, and parents reported that resources offered by centers helped them to cope with stress (Zhang et al, 2021 ).…”
Section: Stress Effects On Children’s Learning and Center-parent Comm...mentioning
confidence: 99%
See 1 more Smart Citation
“…Research undertaken during the pandemic demonstrated that teachers experienced upheaval regarding approaches and methods of teaching (Kim, 2020 ), including the change from in-person to remote learning (Dias et al, 2020 ; Steed & Leech, 2021 ). Important to this investigation, overall teaching experiences (Kim et al, 2021 ), how teachers interacted with students (Szente, 2020 ), and the emotional toll (Bigras et al, 2021 ) of the pandemic additionally burden stressed ECE teachers. As a result, national data indicated that 35% of the ECE workforce was laid off between February and April of 2020 (U.S. Department of Labor, 2022 ).…”
Section: Teacher Stressmentioning
confidence: 99%